Correction: Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanne Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)

Soil health indicator variability and management sensitivity across soils, bioregions, and agricultural systems - Katherine A. Dynarski; Ekundayo Adeleke; R. Louis Baumhardt; Joseph Burke; Tiffany Carter; Paul DeLaune; Huijie Gan; Julie Grossman; Josh Heitman; Divya Kandanool; Katie Lewis; Katherine Naasko; et al. (Agriculture, Ecosystems & Environment, 2026)

Progress status of the NUSES Space Mission - M. Abdullahi; R. Aloisio; S. Ashurov; U. Atalay; F.C.T. Barbato; R. Battiston; M.E. Bertaina; E. Bissaldi; D. Boncioli; L. Burmistrov; I. Cagnoli; E. Casilli; et al. (Advances in Space Research, 2026)

Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanna Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)
We aim to compare clinical practices in the gynecological management of women with Lynch syndrome across Europe and assess the need for multidisciplinary gynecological care for this high-risk population. European gynecologists involved in the clinical care of women with Lynch syndrome were invited to complete a cross-sectional survey regarding their clinical practices and organization of care. All participating gynecologists were based in hospitals that are members of the European Reference Network on Genetic Tumour Risk Syndromes (ERN GENTURIS). A total of 33 gynecologists (57%) from 25 unique hospitals across 12 countries participated in the survey. National guidelines on the gynecological management of women with Lynch syndrome were absent in a significant number of European countries. Local multidisciplinary team meetings were available in 61% of hospitals. Considerable heterogeneity was reported in the organization of care, as well as in surveillance, prevention, and treatment strategies. Standardized European guidelines for the gynecological care of women with Lynch syndrome are warranted to promote uniformity. Gynecologists specialized in hereditary cancer should take the lead in developing and implementing these guidelines. Hospitals managing women with Lynch syndrome should have the resources to organize multidisciplinary team meetings, which are crucial for the effective implementation of these guidelines and the improvement of personalized care.

Early effects of anti-TNFα antibodies in horses with osteoarthritis - G. Perrone; C. Giampaoli; A. Lorenzo Smirnoff; A. Ochoa; R. Pareja; E. De Simone (Journal of Equine Veterinary Science, 2025)

Integrated geophysical and geological surveys reveal new details of the large Montescaglioso (southern Italy) landslide of December 2013 - G. Calamita; M.R. Gallipoli; E. Gueguen; R. Sinisi; V. Summa; L. Vignola; T.A. Stabile; J. Bellanova; S. Piscitelli; A. Perrone (Engineering Geology, 2023)

Seismic risk assessment of masonry-infilled RC building portfolios: impact of variability in the infill properties - G. Mucedero; D. Perrone; R. Monteiro (Bulletin of Earthquake Engineering, 2023)

The Impact of the Parenteral Opioid Medication Shortages on Opioid Utilization Practices in the Emergency Department of Two University Hospitals - Amanda J. Deutsch; David A. Gajdosik; Christine Ramdin; Collin Tebo; Maryann Mazer-Amirshahi; Erin R. Fox; Josh Colorado; Lewis S. Nelson; Jeanmarie Perrone (Journal of Medical Toxicology, 2021)

Nonlinear static characterisation of masonry-infilled RC building portfolios accounting for variability of infill properties - G. Mucedero; D. Perrone; R. Monteiro (Bulletin of Earthquake Engineering, 2021)

Physical stratigraphy and geotechnical properties controlling the local seismic response in explosive volcanic settings: the Stracciacappa maar (central Italy) - M. Moscatelli; G. Vignaroli; A. Pagliaroli; R. Razzano; A. Avalle; I. Gaudiosi; S. Giallini; M. Mancini; M. Simionato; P. Sirianni; G. Sottili; J. Bellanova; et al. (Bulletin of Engineering Geology and the Environment, 2021)
Nowadays, policies addressed to prevention and mitigation of seismic risk need a consolidated methodology finalised to the assessment of local seismic response in explosive volcanic settings. The quantitative reconstruction of the subsoil model provides a key instrument to understand how the geometry and the internal architecture of outcropping and buried geological units have influence on the propagation of seismic waves. On this regard, we present a multidisciplinary approach in the test area of the Stracciacappa maar (Sabatini Volcanic District, central Italy), with the aim to reconstruct its physical stratigraphy and to discuss how subsoil heterogeneities control the 1D and 2D local seismic response in such a volcanic setting. We first introduce a new multidisciplinary dataset, including geological (fieldwork and log from a 45-m-thick continuous coring borehole), geophysical (electrical resistivity tomographies, single station noise measurements, and 2D passive seismic arrays), and geotechnical (simple shear tests performed on undisturbed samples) approaches. Then, we reconstruct the subsoil model for the Stracciacappa maar in terms of vertical setting and distribution of its mechanical lithotypes, which we investigate for 1D and 2D finite element site response analyses through the application of two different seismic scenarios: a volcanic event and a tectonic event. The numerical modelling documents a significant ground motion amplification (in the 1–1.5 Hz range) revealed for both seismic scenarios, with a maximum within the centre of the maar. The ground motion amplification is related to both 1D and 2D phenomena including lithological heterogeneity within the upper part of the maar section and interaction of direct S-waves with Rayleigh waves generated at edges of the most superficial lithotypes. Finally, we use these insights to associate the expected distribution of ground motion amplification with the physical stratigraphy of an explosive volcanic setting, with insights for seismic microzonation studies and local seismic response assessment in populated environments.

Human behavior or taphonomy? On the breakage of Eastern North American Paleoindian endscrapers - Alyssa Perrone; Michael Wilson; Michael Fisch; Briggs Buchanan; Michelle R. Bebber; Metin I. Eren (Archaeological and Anthropological Sciences, 2020)

Buprenorphine Initiation in the Emergency Department: a Thematic Content Analysis of a #firesidetox Tweetchat - Megan Chenworth; Jeanmarie Perrone; Jennifer S. Love; Howard A. Greller; Abeed Sarker; Peter R. Chai (Journal of Medical Toxicology, 2020)

Leadership Roles in Opioid Stewardship and the Treatment of Patients with Opioid Use Disorder Among Medical Toxicologists - Joseph E. Carpenter; Brian Patrick Murray; Maryann Mazer-Amirshahi; JoAn R. Laes; Nicholas Nacca; Lewis S. Nelson; Jeanmarie Perrone; Evan S. Schwarz; Timothy J. Wiegand; Paul M. Wax (Journal of Medical Toxicology, 2020)

The microRNA-29a Modulates Serotonin 5-HT7 Receptor Expression and Its Effects on Hippocampal Neuronal Morphology - Floriana Volpicelli; L. Speranza; S. Pulcrano; R. De Gregorio; M. Crispino; C. De Sanctis; M. Leopoldo; E. Lacivita; U. di Porzio; G. C. Bellenchi; C. Perrone-Capano (Molecular Neurobiology, 2019)

Seismic performance of non-structural elements during the 2016 Central Italy earthquake - D. Perrone; P. M. Calvi; R. Nascimbene; E. C. Fischer; G. Magliulo (Bulletin of Earthquake Engineering, 2019)

Multimodal Neuroimaging in Schizophrenia: Description and Dissemination - C. J. Aine; H. J. Bockholt; J. R. Bustillo; J. M. Cañive; A. Caprihan; C. Gasparovic; F. M. Hanlon; J. M. Houck; R. E. Jung; J. Lauriello; J. Liu; A. R. Mayer; et al. (Neuroinformatics, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Contribution of EARLINET/ACTRIS to the summer 2013 Special Observing Period of the ChArMEx project: monitoring of a Saharan dust event over the western and central Mediterranean - M. Sicard; R. Barragan; C. Muñoz-Porcar; A. Comerón; M. Mallet; F. Dulac; J. Pelon; L. Alados Arboledas; A. Amodeo; A. Boselli; J. A. Bravo-Aranda; G. D’amico; et al. (International Journal of Remote Sensing, 2016)

Mediterranean aerosol typing by integrating three-wavelength lidar and sun photometer measurements - M. R. Perrone; P. Burlizzi (Environmental Science and Pollution Research, 2016)

Impact of desert dust events on short- and long-wave radiation at the surface over south-eastern Italy - S. Romano; M. R. Perrone (Arabian Journal of Geosciences, 2016)

Saharan dust impact on the chemical composition of PM10 and PM1 samples over south-eastern Italy - M. R. Perrone; Alessandra Genga; Maria Siciliano; Tiziana Siciliano; Fabio Paladini; Pasquale Burlizzi (Arabian Journal of Geosciences, 2016)

Spin-off Extreme Value and Archimedean copulas for estimating the bivariate structural risk - R. Pappadà; E. Perrone; F. Durante; G. Salvadori (Stochastic Environmental Research and Risk Assessment, 2016)

Flower and fruit structure of the endangered species Petagnaea gussonei (Sprengel) Rauschert (Saniculoideae, Apiaceae) and implications for its reproductive biology - O. De Castro; P. Colombo; L. Gianguzzi; R. Perrone (Plant Biosystems, 2015)

Columnar and ground-level aerosol optical properties: sensitivity to the transboundary pollution, daily and weekly patterns, and relationships - M. R. Perrone; S. Romano; J. A. G. Orza (Environmental Science and Pollution Research, 2015)

A Review of Emergency Cardiopulmonary Bypass for Severe Poisoning by Cardiotoxic Drugs - Nicholas J. Johnson; David F. Gaieski; Steven R. Allen; Jeanmarie Perrone; Francis DeRoos (Journal of Medical Toxicology, 2013)

A Biomonitoring Study Assessing the Residual Biological Effects of Pollution Caused by the HAVEN Wreck on Marine Organisms in the Ligurian Sea (Italy) - A. Viarengo; F. Dondero; D. M. Pampanin; R. Fabbri; E. Poggi; M. Malizia; C. Bolognesi; E. Perrone; E. Gollo; G. P. Cossa (Archives of Environmental Contamination and Toxicology, 2007)

Neonatal pain analyzer: development and validation - R. Sisto; C. V. Bellieni; S. Perrone; G. Buonocore (Medical & Biological Engineering & Computing, 2006)